Management typologies, organizational satisfaction and performance of selected elementary schools in the National Capital Region - Lacuesta, Loreto Gascon 1924- (1981)
This study collected data from 270 teachers and 29 principals of public and private schools on the perceived and desired management systems. Performance data based on pupil achievement and teacher turnover and pupil dropout rates were obtained from the SOUTELE I Computer tapes and survey form. Satisfaction scores were derived from the mean rating of the desired and perceived systems using Saul's formula. The schools use a consultative System 3 Management with principals perceiving a more participative System 3 than the teachers. Public school teachers perceive participation in the various management processes to be differentially distributed with leadership and Interaction-influence process as the most participative and the communication and decision making processes as the least participative.
Mimeographed.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Vita.
Keywords: Elementary school administration -- Philippines -- Manila metropolitan area; School management and organization -- Philippines -- Manila metropolitan area